Women Amidst the Shackles of Patriarchal Culture: An Analysis of Hadith Regarding Women's Jihad Within the Home - Istianah, Istianah; Nafisah, Lailiyatun (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This research departs from anxiety about the position of women in the household. Moreover, there are hadith texts which state that women's jihad is in the house. The purpose of this research is to understand how the meaning of jihad contained in the hadith text relates to the jihad of women in the house. This research is a qualitative type by examining and studying the hadith texts about women's jihad in the house using the mubilah (mutuality) method of Kiai Faqihuddin Abdul Kadir. The results of this study indicate that the concept of jihad in the hadith text is neutral and reciprocal. Jihad is all efforts that are carried out with sincerity so as to bring goodness both inside and outside the home. So, all service work both in the domestic sphere and in the social sphere is jihad, both carried out by men and women. Men and women are partners in realizing good and preventing evil. So that the meaning of jihad contained in the text of the hadith cannot be understood by actually housing women so that public space is only dominated by men